(3GdEOGQI GdeGdjI GdLRA GdKGfj s - (3EdjGS(B, (3Hf SGSjs; (3jhSa bQjTj(B, s ((3YeGf(B:s (3OGQ hGFd ddfTQ hGdJhRjY(B,s, 2011)
(3eONd JYQjaj HGdeDSSI h eONd ddJSjjQ GdeGdj, GdJMdjd GdeGdj GdSGcf h GdJMdjd GdeGdj GdeJMQc, GdSjGSI GdeGdjI h BdjGJ GJNGP GdbQGQGJ GdJehjdjI h GdGSJKeGQjI, fXQjGJ Gdgjcd GdeGdj, Shb GdChQGb GdeGdjI h JSjjQ GdeNGWQ, JPcjQ Hcd GdaUhd GdhGQOI aj GdLRA GdChd eY hLhO CSFdI h GLhHIs
(3HHdjhZQGajG(B: (3U(B.351s
Keywords: (3GdEOGQI GdeGdjIs; (3GdESJKeGQs; (3GdJehjds